Study of accelerated degradation of pigmented UV-cured print inks - Gonçalves Bardi; Marcelo Augusto; Luci Diva Brocardo Machado (Journal of Graphic Engineering and Design, 2013)
Print inks have assumed an important role on finished materials, such as plastic packages, which can have a long lifetime when disposed as municipal waste. By this way, it is important to evaluate the influence of physical parameters on the degradation of shot lifetime substrates covered by pigmented print inks cured by UV radiation.